ANALISIS EKSPOR JAHE DARI JAWA TENGAH - Sri Budiarti; Heru Irianto (Universitas Sebelas Maret, 2005)
The research aims to know factors that influance ginger export from Central Java and supply elasticity of ginger export. Basic method used in the research is descriptive analytis and area sampling with puposive. Analysis method use non linear regretion model